A critical realism view of design artefact knowledge. (1st January 2013) - Wang, Wenjuan; Duffy, Alex; Boyle, Iain; Whitfield, Robert Ian
Design artefact knowledge elements and their relationships have been presented in previous work. Aiming to explore the existence of these elements from a critical realism view, this paper presents a new model of function-behaviour-structure (CR-FBS) based on protocol analysis of a design project. Three fundamental artefact knowledge elements, i.e., function, behaviour, and structure, and their causal relationships are re-presented in the CR-FBS illustrating the recursive nature of artefact knowledge evolution. These elements are presented as being distributed across three design artefact knowledge spaces: expected, instantiated, and interpreted. The critical realism perspective has highlighted that rather than being inherent in all of the three spaces, function only exists in the expected and interpreted design artefact knowledge space, and structure only exists in the expected and instantiated design artefact knowledge space. Consequently, causal relationships among function, behaviour, and structure are limited to where the three fundamental artefact knowledge elements exist.